PENGARUH KEBIJAKAN DIVERSIFIKASI DAN KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN BUMN JASA KONSTRUKSI - Eddy Irsan Siregar (Faculty of Economic and Business, 2012)
The aim of this study is to obtain the influence of diversification policy and firm’s characteristics to the construction state owned enterprises (SOEs) firm’s value. The firm’s characteristics on this study are based on firm size, growth opportunities, and agency costs on some construction state-owned enterprise in Indonesia. The analysis method used in this research was panel data regression. These results indicate that the value of the company was affected by the company characteristic and it diversification. The entire independent variables such as diversification, firm size, growth opportunities, and agency costs had a significant effect on firm value. Business diversification and agency costs had a negative impact on firm value. Firm size and growth opportunities had a positive effect on firm value.DOI: 10.15408/etk.v11i1.1869